New Zealand's rural hospitals in 2021: findings from an exploratory questionnaire survey - Tim Stokes; Ray Anton; Lauralie Richard; Sue Crengle; Garry Nixon; Rory Miller; Lynne Clay; Katharina Blattner (CSIRO Publishing, 2022)
Introduction There is a gap in our knowledge of the place and contribution of rural hospitals in the New Zealand health system. There is no current description of rural hospital services, no national policies and little published research regarding their value. Aim To explore rural hospital leader perspectives of the role of rural hospitals. Methods An on-line survey of rural hospital leaders conducted to capture perspectives on areas including facility nomenclature; access and equity; funding and the health reforms. Results Fifty-five rural hospital leaders representing 19/24 rural hospitals responded. 'Rural Hospital' was the most common term used to describe facilities with 80% of respondents indicating this as their preferred term. Other descriptive terms varied widely from primary through to secondary care. Respondents indicated that the loss of rural hospital in-patient beds would be unacceptable to communities (median 0, IQR 0, 1). Scores on questions about 'range of services' (median 7, IQR 6, 8), 'accessibility' (median 7, IQR 6, 8) and how rural hospitals were addressing health equity (median 6, IQR 5, 7) were variable. The process for allocating funds to rural hospitals was perceived as lacking transparency (median 3, IQR 2, 5). National strategy and 'local governance and control' were both rated as important (median 9, IQR 7, 10 and median 9, IQR, 8, 10) for a rural hospital's future. Discussion By capturing a collective national rural hospital leadership voice, this study facilitates the understanding of the rural hospital concept. The findings inform subsequent research needed to gain a clearer picture of New Zealand rural hospital provision.